Profile, climate change awareness and adaptation level of residents in selected municipalities in Cavite - Rogando, Vivian D.; Signo, Cristina M. (2014)
This research was conducted to determine the profile, climate change awareness and adaptation level of residents in selected municipalities in Cavite. The relationships among the variables were also determined. This study employed descriptive-correlational design. The municipalities included are Cavite City, Kawit, Noveleta, Rosario, Bacoor and Imus. The respondents were 30-60 year old with 5 years minimum residency in one of the mentioned municipalities. A total of 946 respondents participated in the study. Simple random technique and convenience sampling were used in selecting the participants. A validated survey questionnaire was utilized as the main research instrument. Results revealed that the participants are mainly comprised of those who were aged 30-35, able to study in colleg, female and employed. They have high level of awareness on climate change and avarage level of climate change adaptation. Educational attainment, gender and employment were found to be significantly related to climate change awareness while age did not significantly influence awareness. Gender and employment significantly influence adaptation level while age and educational attainment were not related to adaptation. Climate change awareness and climate change adaptation were not significantly related. Adaptation to climate change is not dependent on climate change awareness. Individuals can adapt to changes in climate even though he is not knowledgeable about it. Likewise, being highly aware about changes in climate does not guarantee high adaptive strategies.
Keywords: Climate change